Ecological niche and bet-hedging strategies for Triodia (R.Br.) seed germination - Lewandrowski, W.; Erickson, T.; Dalziell, Emma; Stevens, J. (Oxford University Press, 2018)
Background and Aims: Regeneration dynamics in many arid zone grass species are regulated by innate seed dormancy mechanisms and environmental cues (temperature, moisture and fire) that result in infrequent germination following rainfall. This study investigated bet-hedging strategies associated with dormancy and germination in arid zone Triodia species from north-west Australia, by assessing (1) the effects of the mechanical restriction imposed by the indehiscent floral bracts (i.e. floret) covering the seed and (2) the impact of dormancy alleviation on florets and cleaned seeds (i.e. florets removed) when germinated under water stress. Methods: The initial dormancy status and germination for six species were tested on intact florets and cleaned seeds, across temperatures (10–40 °C) with and without the fire-related stimulant karrikinolide (KAR1), and under alternating light or constant dark conditions. Physiological dormancy alleviation was assessed by wet/dry cycling florets over a period of 10 weeks, and germination was compared against untreated florets, and cleaned seeds across a water potential gradient between 0 and –1.5 MPa. Key Results: Florets restricted germination (<45 %) at all temperatures and, despite partial alleviation of physiological dormancy (wet/dry cycling for 8 weeks), intact florets germinated only at high water potentials. Cleaned seeds showed the highest germination (40–90 %) across temperatures when treated with KAR1, and germinated at much lower water potentials (–0.4 and –0.9 MPa). Triodia pungens was the most responsive to KAR1, with both seeds and florets responding, while for the remaining five species, KAR1 had a positive effect for seeds only. Conclusions: Only after seed dormancy was alleviated by removing florets and when KAR1was applied did germination under water stress increase. This suggests that seeds of these Triodia species are cued to recruit following fire and during periods of high precipitation. Climate change, driven by large shifts in rainfall patterns, is likely to impact Triodia recruitment further in arid zone grasslands.